The Parable of the Sower: a case study examining the use of the Godly Play® method as a spiritual intervention on a psychiatric unit of a major children's hospital - Minor, Cheryl V. (International journal of children's spirituality, 2016)
This case study examines the use of Godly Play® as a pastoral intervention on a psychiatric unit at Children's Health - Children's Medical Center in Dallas, Texas. The chaplain adapts Godly Play®, more typically used as a programme of Christian formation in churches and schools, for this setting, leading a Purpose and Meaning' group weekly whose goal is to provide inpatients with a developmentally appropriate way of reflecting on and expressing their own sense of identity, purpose and meaning within the personal, social and spiritual milieu in which they identify themselves as members. The case study examines how the method is adapted as a spiritual intervention in a clinical setting, and analyses its effectiveness in meeting the stated goals of the group.